Investigating the Streptococcus sinensis competence regulon through a combination of transcriptome analysis and phenotypic evaluation. Issue 10 (25th October 2022) - Brennan, Alec A.; Harrington, Anthony; Guo, Mingzhe; Renshaw, Clay P.; Tillett, Richard L.; Miura, Pedro; Tal-Gan, Yftah
Abstract : Streptococcus sinensis is a recently identified member of the Mitis group of streptococci. This species has been associated with infective endocarditis; however its mechanisms of pathogenesis and virulence are not fully understood. This study aimed to investigate the influence of the competence-stimulating peptide (CSP) and the competence regulon quorum-sensing circuitry (ComABCDE) on subsequent gene transcription and expression, as well as resultant phenotypes. In this study we confirmed the native CSP identity, ascertained when endogenous CSP was produced and completed a transcriptome-wide analysis of all genes following CSP exposure. RNA sequencing analysis revealed the upregulation of genes known to be associated with competence, biofilm formation and virulence. As such, a variety of phenotypic assays were utilized to assess the correlation between increased mRNA expression and potential phenotype response, ultimately gaining insight into the effects of CSP on both gene expression and developed phenotypes. The results indicated that the addition of exogenous CSP aided in competence development and successful transformation, yielding an average transformation efficiency comparable to that of other Mitis group streptococci. Additional studies are needed to further delineate the effects of CSP exposure on biofilm formation and virulence. Overall, this study provides novel information regarding S. sinensis and provides a substantial foundation on which this species and its role in disease pathogenesis can be further investigated.